2011
DOI: 10.1002/stem.698
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Interferon-γ Enhances the Therapeutic Activity of Mesenchymal Stromal Cells in Animal Models of Colitis

Abstract: Mesenchymal stromal cells (MSCs) are currently under investigation for the treatment of inflammatory disorders, including Crohn's disease. MSCs are pluripotent cells with immunosuppressive properties. Recent data suggest that resting MSCs do not have significant immunomodulatory activity, but that the immunosuppressive function of MSCs has to be elicited by interferon-c (IFN-c). In this article, we assessed the effects of IFN-c prestimulation of MSCs (IMSCs) on their immunosuppressive properties in vitro and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
201
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(210 citation statements)
references
References 43 publications
6
201
1
2
Order By: Relevance
“…Sun et al reported similar fi ndings with UC-MSCs transplantation in patients with refractory SLE 3 months after treatment, also suggesting a polarization toward the Th1 phenotype, that was associated with clinical improvement . In gastrointestinal models of disease, pretreatment of MSCs with IFN-γ markedly inhibited dextran sodium sulfate (DSS) induced colitis in mice, leading to improvement of body weight, colitis scores and better survival rates compared to untreated mice (Duijvestein et al, 2011). Recent studies have suggested that Toll Like Receptor (TLR) signaling regulates the proliferation, diff erentiation and immune function of MSCs.…”
Section: Tipping Of the Th1/th2 Balancementioning
confidence: 99%
“…Sun et al reported similar fi ndings with UC-MSCs transplantation in patients with refractory SLE 3 months after treatment, also suggesting a polarization toward the Th1 phenotype, that was associated with clinical improvement . In gastrointestinal models of disease, pretreatment of MSCs with IFN-γ markedly inhibited dextran sodium sulfate (DSS) induced colitis in mice, leading to improvement of body weight, colitis scores and better survival rates compared to untreated mice (Duijvestein et al, 2011). Recent studies have suggested that Toll Like Receptor (TLR) signaling regulates the proliferation, diff erentiation and immune function of MSCs.…”
Section: Tipping Of the Th1/th2 Balancementioning
confidence: 99%
“…Preclinical studies on the models of necrotizing colitis as well as experimental colitis induced by DSS and 2,4,6-TNBA showed positive effect of systemic and local use of MSC derived from the bone marrow, amniotic fluid, cord blood, adipose tissue on the course of colitis and stimulation of reparation [15,16,19,26]. CT was shown to increase survival and stimulate reparation of the damaged mucous membranes of the large intestine of newborn rats with necrotizing colitis.…”
Section: Discussionmentioning
confidence: 98%
“…Prestimulation with a cocktail of five cytokines containing fms-like tyrosine kinase 3 (Flt-3) ligand, stem cell factor (SCF), interleukin (IL)-6, HGF, and IL-3 promotes the migration of FLK(+) MSCs to the bone marrow through up-regulation of both cell surface and intracellular CXCR4 [71] . Other factors, such as IGF-1 [72,73] , IL 1β [74] , interferon γ (IFNγ) [4,75] , basic fibroblast growth factor (bFGF), PDGF [41] , nitric oxide donor [76] , or complement 1q (C1q) [77] have also been shown to improve MSC homing in different disease models possibly as a result of increased CXCR4 or MMP expression. Pretreating MSCs with a combination of hematopoietic growth factors erythropoietin (EPO) and granulocyte colony stimulating factor (G-CSF) can enhance their motility by increasing the MMP expression [78] .…”
Section: Pretreatment Of Mscs With Cytokines and Small Moleculesmentioning
confidence: 99%